A Stage Model of Social Media Adoption - Duane, Aidan; O’Reilly, Philip (Journal of Advances in Management Sciences & Information Systems, 2016)
There is very little understanding of how organisations manage social media. In particular, there is no established path of activities that guide a company down the path of social readiness, and the management and organisation of social media is under-researched. Consequently, many organisations experience significant problems with their social media business profiles (SMBP). Stage of growth (SoG) models represent a picture of evolution, where the current stage can be understood in terms of history and future, providing an opportunity to identify the stages, paths of evolution, benchmark variables, and dominant problems experienced by organisations at each stage. Following a review of four decades (1974-2014) of SoG model research, and a review of existing social media research and practitioner insight across multiple domains, the authors adopt Gottschalk and Solli-Saether’s (2010) [1] five step Stage Modelling Process as a research methodology to develop a stage model of SMBP implementation and management. The paper analyses the findings from Step 1 (Suggested Stage Model) and Step 2 (Conceptual Stage Model) of the Stage Modelling Process, before concluding with the key findings. This research contributes to academia by enhancing the existing four decades of knowledge of SoG models, extending it to the management of social media in an organisational context. This research is also a critical piece of research from a practitioner perspective, as organisations struggle to devise tactics and strategies to manage social media adoption and use.